Illness Perceptions Explain the Variance in Functional Disability, but Not Habitual Physical Activity, in Patients With Chronic Low Back Pain: A Cross‐Sectional Study. Issue 4 (26th October 2017) - Leysen, Marijke; Nijs, Jo; Van Wilgen, C. Paul; Struyf, Filip; Meeus, Mira; Fransen, Erik; Demoulin, Christophe; Smeets, Rob J.E.M.; Roussel, Nathalie A.
Abstract: Introduction: Although the importance of psychosocial factors has been highlighted in many studies in patients with chronic low back pain (CLBP), there is a lack of research examining the role of illness perceptions in explaining functional disability and physical activity in patients with CLBP. Aim: The aim of the study was to explore the value of illness perceptions in explaining functional disability and physical activity in patients with CLBP. Methods: Eighty‐four participants with CLBP (of > 3 months' duration) completed a battery of questionnaires investigating psychosocial factors (Pain Catastrophizing Scale [PCS], Illness Perceptions Questionnaire Revised [IPQ‐R], and 36‐Item Short Form mental health scale [SF‐36_MH]) and perceived pain intensity (visual analog scale [VAS]), as well as the Oswestry Disability Index (ODI) and Baecke questionnaire. The latter 2 were entered separately as dependent variables in a regression analysis. Results: The combined variables (VAS, PCS, SF‐36_MH, IPQ‐R) accounted for 62% of the variance in functional disability (ODI). Adding the results of the IPQ‐R to the scores of the other 3 variables (VAS, PCS, SF‐36_MH) significantly increased the explained variance of ODI scores in CLBP patients, yielding 18% additional information ( P  <   0.01). Only 5% of the variance in the Baecke questionnaire was explained by combining the 4 variables. None of the single variables alone made a significant contribution to R ². Conclusions: Illness perceptions are an important factor for explaining functional disability, but not for explaining habitual physical activity in CLBP patients.